Plant Growth Promoting Rhizobacteria (PGPR): Reports on Their Colonization, Beneficial Activities, and Use as Bioinoculant - Dew Biswas; Amit Kumar Chakraborty; Vikas Srivastava; Arunava Mandal (Advances in Agriculture)
Recurring use of chemical fertilizers (CFs) in agriculture has resulted the remarkable improvement in crop productivity but their ruinous effects on environment have made a serious issue. Biological entities (e.g., several microorganisms) showing fertilizer-like activities have gained attention in this regard. Several soil resident microorganisms interact strongly with neighboring plants and promote the growth and development of those plants through various means. In exchange of this, microbes utilize different compounds released from plant roots for their own nutrition. This mutualistic mode of interrelation predominantly relies on the transmission of signals from microbes to plants and vice versa. However, climatic factors (e.g., CO2 level, temperature, and water availability) are also important for this association. These bacterial strains are literally known as plant growth promoting rhizobacteria (PGPR) which facilitate plant growth through nitrogen fixation, mineral solubilization, phytostimulation, stress resistance, etc. Responding to the external environmental stimuli, they often modulate the expression of genes responsible for the transport of nutrients. Reduction of the use of CFs through the application of PGPR strains in the cultivation of some economically important plants has been reported by several authors. Significant yield improvement compared to the control groups was found in all experimental studies. Commercial development of the PGPR inoculants with remarkable biostimulating activities and their successive application should be expanded through collaborative association with different sectors after the removal of existing lacunae. Reading more than 100 articles on various aspects of rhizobacteria, the plan of writing this article has been executed. In this review, we have discussed about the colonization and potency of PGPR strains and how their well-planned application in agriculture could evidently reinforce the global economy. The main structure of this text is designed as an outline from the development of interrelation between plants and PGPR to the commercialization of PGPR based on their potential role in the field of agriculture.